2005
DOI: 10.1016/j.ophtha.2005.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and Heritability of Intraocular Pressure and Cup-to-Disc Ratio in a Defined Older Population

Abstract: Purpose-To investigate the heritability of intraocular pressure (IOP) and cup-to-disc ratio (CDR) in an older well-defined population. Design-Family-based cohort study.Participants-Through the population-based Salisbury Eye Evaluation study, we recruited 726 siblings (mean age, 74.7 years) in 284 sibships.Methods-Intraocular pressure and CDR were measured bilaterally for all participants. The presence or absence of glaucoma was determined by a glacuoma specialist for all probands on the basis of visual field, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
1
7

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(65 citation statements)
references
References 64 publications
(49 reference statements)
1
56
1
7
Order By: Relevance
“…Large studies of twins, siblings, and small pedigrees have shown that CCT, 76,77 cup-to-disc ratio, [78][79][80][81] and IOP [80][81][82][83][84] are all highly heritable traits and are likely determined in part by the actions of genes. Investigations to identify these genes will likely provide important insights into the pathophysiology of glaucoma.…”
Section: Quantitative Traits Approaches To the Genetics Of Poagmentioning
confidence: 99%
“…Large studies of twins, siblings, and small pedigrees have shown that CCT, 76,77 cup-to-disc ratio, [78][79][80][81] and IOP [80][81][82][83][84] are all highly heritable traits and are likely determined in part by the actions of genes. Investigations to identify these genes will likely provide important insights into the pathophysiology of glaucoma.…”
Section: Quantitative Traits Approaches To the Genetics Of Poagmentioning
confidence: 99%
“…1 Although it no longer forms part of the definition of the disease, elevated intraocular pressure (IOP) is the principal modifiable risk factor for the development and progression of open-angle glaucoma. [2][3][4] Although the Goldmann applanation tonometer (GAT) has been the 'gold standard' for measuring IOP in the clinical setting for several decades, recently there has been a growing interest in developing new technology to measure a more accurate IOP. 5 It is well known that GAT is affected by the central corneal thickness (CCT).…”
Section: Introductionmentioning
confidence: 99%
“…Um estudo genético da relação E/D entre parentes de primeiro grau relatou correlação altamente sugestiva de herança poligênica multifatorial (10) . Mais recentemente, Chang et al consideraram que a relação E/D em parentes de glaucomatosos era 0,07 (19%) maior que em parentes de probandos normais (p= 0,004) (11) . Existe controvérsia se discos ópticos maiores correlacionam-se com maior risco de dano glaucomatoso.…”
Section: Discussionunclassified
“…As diferenças observadas entre o grupo 1 e o grupo 3 reafirmam a noção de que um aumento na relação E/D em parentes próximos de portadores de glaucoma, possa ser realmente um traço herdado mais que puramente adquirido. Entretanto, sabe-se que a pressão intraocular permanece como importante fator de risco para a doença, também com hereditariedade estimada em 0,29 com diferença média de 1,02 mmHg (p=0,017) para mais em parentes de probandos com a doença (11) . Porém, não encontramos diferenças estatisticamente significantes para a pressão intraocular e espessura corneana central entre os grupos, fato esse justificado talvez pelo tamanho reduzido da amostra.…”
Section: Discussionunclassified